Petrological study of the migmatites of the Nordmannwick nappe - Voltolini, Francesco (2022)
This work is a petrological research on the partial melting of metapelitic rocks, and includes a petrographic-microstructural study, a bulk- and microchemical characterization, and the thermodynamic modelling of phase equilibria. The Nordmannwick nappe is a high grade tectonic unit occurring structurally below the Lyngen Ophiolite (Northern Scandinavian Caledonides, Northern Norway). This unit is compositionally heterogeneous (metapelitic schists, metapsammites, carbonatic layers, mafic bodies) but it is clearly characterized by the occurrence of high grade metamorphic imprint with the formation of migmatites. Two samples of migmatites (LY4f and LY131) belonging to this high grade portion were studied. The metapelitic sample LY4f shows relicts of kyanite porphyroblasts and a peak mineral assemblage constituted by biotite + garnet + plagioclase + quartz + sillimanite + former melt. The mineral assemblage formed after the retrogression is biotite + white mica + garnet + plagioclase + quartz + sillimanite. The metapsammitic sample LY131 is characterized by the presence of partially replaced kyanite crystals and by a peak mineral assemblage constituted by biotite + garnet + K-feldspar + plagioclase + quartz + sillimanite + former melt, whereas the mineral assemblage formed after the retrogression is biotite + white mica + garnet + plagioclase + quartz + sillimanite. A sequence of three main metamorphic events is detected by means of microstructural observations and electron microprobe analyses for both samples. The first one is a high pressure event, followed by a high temperature melt-bearing event. The last metamorphic event occurs during retrogression. Phase equilibria modelling, performed with Perple_X in the MnO – Na2O – CaO – K2O – FeO – MgO – Al2O3 – SiO2 – H2O – TiO2 (MnNCaKFMASHT) system, was applied to sample LY4f and LY131. The temperature and the pressure estimated for sample LY4f at the peak conditions are 800±30° and 0.85±0.07 GPa, whereas after the retrogression are 650±30° and 0.77±1.8 GPa. The ...